ФОРМУВАННЯ ГОТОВНОСТІ СТУДЕНТІВ ДО САМООСВІТИ ЯК АКТУАЛЬНА ПЕДАГОГІЧНА ПРОБЛЕМА (Педагогіка вищої та середньої школи, 2010)
This article deals with one of the most important problems in the sphere of education now - the problem of formation of readiness of students to the self-education.